Colonization and Internalization of Salmonella enterica and Its Prevalence in Cucumber Plants - Burris, Kellie P.; Simmons, Otto D.; Webb, Hannah M.; Deese, Lauren M.; Moore, Robin Grant; Jaykus, Lee-Ann; Zheng, Jie; Reed, Elizabeth; Ferreira, Christina M.; Brown, Eric W.; Bell, Rebecca L. (Frontiers in Microbiology, 2020)
Consumption of cucumbers (Cucumis sativus var. sativus) has been linked to several foodborne outbreaks involving Salmonella enterica. The purpose of this work was to investigate the efficiency of colonization and internalization of S. enterica into cucumber plants by various routes of contamination. Produce-associated outbreak strains of Salmonella (a cocktail of serovars Javiana, Montevideo, Newport, Poona, and Typhimurium) were introduced to three cultivars of cucumber plants (two slicing cultivars and one pickling) via blossoms (ca. 6.4 log10 CFU/blossom, 4.5 log10 CFU/blossom, or 2.5 log10 CFU/blossom) or soil (ca. 8.3 log10 CFU/root zone) and were analyzed for prevalence of Salmonella contamination (internal and external) and serovar predominance in fruit and stems. Of the total slicing fruit harvested from Salmonella-inoculated blossoms (ca. 6.4, 4.5, or 2.5 log10 CFU/blossom), 83.9% (47/56), 81.4% (48/59) or 71.2% (84/118) were found colonized and 67.9% (38/56), 35.6% (21/59) or 22.0% (26/118) had Salmonella internalized into the fruit, respectively. S. Poona was the most prevalent serovar isolated on or in cucumber fruits at all inoculation levels. When soil was inoculated at 1 day post-transplant (dpt), 8% (10/120) of the plants were shown to translocate Salmonella to the lower stem 7 days post-inoculation (dpi). Results identified blossoms as an important route by which Salmonella internalized at a high percentage into cucumbers, and S. Poona, the same strain isolated from the 2015 outbreak of cucumbers imported from Mexico, was shown to be well-adapted to the blossom niche.